Treadmill training prevents bone loss by inhibition of PPARγ expression but not promoting of Runx2 expression in ovariectomized rats - Chen, Yongjie; Wang, Shouhui; Bu, Shumin; Wang, Yingjie; Duan, Yushuang; Yang, Shaofeng (European journal of applied physiology, 2011)
Exercise training has been reported to prevent bone loss in ovariectomized (OVX) rats and postmenopausal women. We hypothesized that treadmill training inhibited adipogenesis and enhanced osteogenesis through the regulation of adipocyte differentiation factor peroxisome proliferators-activated receptor gamma (PPARγ) and the osteogenic factor runt-related transcription factor 2 (Runx2) in a model of OVX-induced osteoporosis. To test this hypothesis, 3-month-old female Sprague–Dawley rats were divided randomly into the following groups: Sham, OVX, OVX exercised (EX), and OVX estrogen replacement (E 2 ). At the end of the experiment, the bone mineral density (BMD) was detected using DEXA and the morphology change of bone tissues and uterus was observed by HE staining. The protein expression for PPARγ and Runx2 were measured by immunohistochemistry and western blot and the bone triacylglycerol (TG) was extracted by methanol/chloroform. OVX dramatically increased the number of fat vacuoles, protein levels for PPARγ and Runx2 as well as the TG level in tibiae and lumbar vertebrate. In contrast, the serum level of E 2 , the lumbar vertebrate BMD as well as the proximal and distal femur BMD was significantly decreased in the OVX group. All changes induced by OVX were significantly reversed by exercise treatment except for the protein expression level of Runx2. Moreover, exercise treatment produced no estrogenic effects on uterus as evidenced by the uterus wet weight and histology. Treadmill training could prevent bone loss induced by OVX through the inhibition of adipocyte differentiation factor PPARγ rather than promoting osteogenic factor Runx2.